Tinjauan Yuridis Perlindungan Hukum terhadap Korban dan Pelaku Kejahatan Berdasarkan Asas Equality Before the Law - Maria Odilia Kolo; Aksi Sinurat; Karolus Kopong Medan (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2024)
The purpose of this research is a juridical review of legal protection of victims and perpetrators of crime based on the principle of equality before the law. This research method is normative law to answer these two main problems. This normative type of research uses qualitative analysis by explaining existing data with words or statements not with numbers. The result of this research is that the legal protection of crime victims based on the principle of equality before the law in its implementation is considered still not good or not optimal, because the protection efforts given to victims are very minimal and the guarantee of legal protection for victims or witnesses is not strictly regulated in the Criminal Procedure Code. The results showed that the legal protection given to the perpetrators of crime when compared to victims of crime has been given optimally but juridically it is still not optimal, because the legal process for the perpetrators of crime has not been applied in its entirety according to the principle of equality before the law and in law enforcement is still based on evidence not on the criminal offense that has been committed by the perpetrator.